ISLAMIC CULTURAL APPROACH IN TEACHING ENGLISH: Dalmeri, Universitas Indraprasta PGRI Jakarta, dalmeri300@gmail.com - Dalmeri Dalmeri (Universitas Putera Batam, 2014)
This paper analyzes the cultural approach to language learning is taught in English. A foreign language teacher has a responsibility to implement most of approaches above mention in order to socialize the language learners into what members of the target language society consider being linguistically and socio culturally appropriate behavior. Consequently, a successful language learner must be adapted in the culture (acculturation) of the target language.